Ichthyosis fetalis in Polled Hereford and Shorthorn calves. (November 2017) - O'Rourke, Brendon A.; Kelly, Jillian; Spiers, Zoe B.; Shearer, Patrick L.; Porter, Naomi S.; Parma, Pietro; Longeri, Maria
Inherited forms of ichthyosis, or generalized scaling of the skin, have been reported in many animal species, including cattle, and are characterized by an autosomal recessive mode of inheritance. We investigated 2 calves affected with ichthyosis fetalis, a Polled Hereford and a Shorthorn. Both cases had hard white plaques on the skin consistent with excessive keratinization. This was confirmed by histopathology, which showed severe diffuse epidermal and follicular orthokeratotic hyperkeratosis. The known mutation (H1935R) in gene ABCA12, responsible for ichthyosis fetalis in Chianina cattle, was shown to be absent in both affected calves and their obligate heterozygous parents. These molecular findings indicate that allelic heterogeneity exists for this condition in cattle.